Análise pelo método da difusão radial da ação antimicrobiana do cimento Portland puro e acrescido de antibióticos - Rocha Junior, Hernando Valentim da (2013)
Due to a lower antimicrobial activity of MTA (Mineral Trioxide Aggregate) in relation to some sealers would be of great value an increase in their antimicrobial activity. Given similarity of the composition, mechanical and biological properties, there is a trend in current research is to use Portland cement there is a tendency in current research analyzing the performance of Portland cement in place the MTA. Facing the benefits of adding an antimicrobial cements to overcome its drawbacks, since it has a weight ratio not exceeding 10%, sounds a good idea to incorporate anantimicrobial Portland cement, increasing thus the benefits of clinical utilization of cement to fill root canals and / or retrograde filling. This study evaluated the antimicrobial activity of pure Portland cement and zirconium oxide as radiopacifiers agent in a proportion of 50% by mass, after the addition of two types of antibiotics amoxicillin and ciprofloxacin, opposite the 5 types of microorganisms generally involved in a maxillofacial infection: S. aureus, P. aeruginosa, E. coli, E. faecalis and C. albicans. For this experiment we used 15 Petri plates prepared with the Mueller- Hinton agar, and sixth wells excavated where the cements were introduced immediately after manipulation. Another 15 plates were prepared in a similar manner where the basic difference was the introduction of the cement after 24 hours of prey. Thus, the performance of Portland cement as a vehicle for antibiotics was evaluated comparatively in vitro. The results showed an inhibitory activity against C. Portland Cement albicans. When the cement plus ciprofloxacin showed antibacterial activity on all the bacteria tested, both pre and post prey, a fact that did not occur when amoxicillin was associated with the cement, since only showed inhibitory activity against E. coli and S. aureus before and after and arrested against E. faecalis only in pre prey In conclusion, there was obtained an increase of antimicrobial activity of the cement after adding antibiotics, particularly ciprofloxacin, and it was shown that addition of radiopacificador agent does not influence the antimicrobial activity of the compositions of Portland cement tested.